Cyclic nucleotide permeability through unopposed connexin hemichannels - Valiunas, Virginijus (Frontiers in Pharmacology, 2013)
Cyclic AMP is a well-known intracellular and intercellular second messenger. The membrane permeability of such molecules has potential importance for autocrine like or paracrine-like delivery. Here experiments have been designed to demonstrate whether gap junction hemichannels, composed of connexins, are a possible entrance pathway for cyclic nucleotides into the interior of cells. HeLa cells stably expressing connexin43 (Cx43) and connexin26 (Cx26) were used to study the cyclic nucleotide permeability of gap junction hemichannels. For the detection of cAMP uptake, the cells were transfected using the cyclic nucleotide-modulated channel from sea urchin sperm (SpIH) as the cAMP sensor. SpIH derived currents (Im) were recorded in whole cell/perforated patch clamp configuration. Perfusion of the cells in an external K+ aspartate- (KAsp) solution containing 500 µM cAMP and no extracellular Ca2+, yielded a 5-7 fold increase in the Im current level. The SpIH current increase was associated with detectable hemichannel current activity. Depolarization of cells in Ca2+-free NaCl perfusate with 500 μM cAMP also induced a SpIH current increase. Elevating extracellular Ca2+ to mM levels inhibited hemichannel activity. Perfusion with a depolarizing KAsp solution containing 500 µM cAMP and 2 mM Ca2+ did not increase SpIH currents. The addition of the gap junction blocker carbenoxolone to the external solution inhibited cAMP uptake. Both cell depolarization and lowered extracellular Ca2+ increase the open probability of non-junctional hemichannels. Accordingly, the SpIH current augmentation was induced by the uptake of extracellular cAMP via open membrane hemichannels in Cx43 and Cx26 expressing cells. The data presented here show that hemichannels of Cx43 and Cx26 are permeable to cAMP, and further the data suggest that hemichannels are, in fact, a potential pathway for cAMP mediated cell-to-cell signaling.